Recommendation of an ideal mixed fluid preparation to be used as partial parenteral nutrition in surgical Neonatal Intensive Care Unit - Ghosh, Arindam; Basak, Anirudhdha; Pramanik, Dibyarup Datta; Mishra, Prafulla Kumar (International Journal of Contemporary Pediatrics, 2020)
Background: This study was conducted to assess the role of Partial Parenteral Nutrition (PPN) and a specially prepared “mixed fluid formula” used as PPN in sick surgical neonates. Methods: This single institution based Randomised Control Trial was performed in Surgical NICU of a tertiary care Centre. Surgical neonates who required bowel rest for >3 days like Esophageal Atresia (22), Duodenal Atresia (38), Jejuno-Ileal Atresia (50), Necrotising Enterocolitis (29) and others (11), were chosen. As a CONTROL population half (75) neonates were allowed maintenance fluid only (Isolyte P) and rest (75) were given a combination of maintenance fluid (Isolyte P) and PPN (specially prepared mixed fluid). This mixed fluid each 100 ml was prepared with 65ml Isolyte P, 15 ml 25% Dextrose, 10 ml Normal Saline, 7 ml Astymin 3, 2 ml Multivitamin and 1 ml Injection KCl. Fluid was continued till enteral feeding was established. Results: Neonates according to their body weight were divided in three groups <1 kg (50), 1-2.5 kg (71) and >2.5 kg (29) and their post-operative outcome was assessed as Clinical Positive/Negative and Laboratory Positive/Negative. Results were separately assessed in 3 body weight groups under “Control” and “Study” which showed both Clinical and Biochemical improvement in “Study group”. Conclusions: The composition of mixed fluid, its nutritional value, calorie supplementation, compatible osmolarity for peripheral venous administration and most importantly its easy and cost-effective preparation were assessed thoroughly and we recommend this “mixed fluid” preparation as a very useful PPN for sick surgical neonates.